Les traductions en langue vernaculaire de la Detectio de George Buchanan - Armel Dubois-Nayt (Etudes Epistémè)
This article looks at the translations of the De Maria Scotorum Regina (1571) and questions the widely accepted assumptions made about these texts. It focuses on the English and Scottish translations of the attack on Mary Queen of Scots, which is centred on her involvement in the murder of her second husband, Henry Darnley. It challenges the idea that the original text was disguised in fake Scottish (“sham Scots”) to hide the fact that William Cecil and Elizabeth Tudor secretly engineered a campaign of disparagement against Mary Queen of Scots. With this aim in mind, this paper carries out a lexical and linguistic analysis of these translations based on other vernacular texts by Buchanan, as well as on those printed in Scotland around the same time. Through a comparative approach, this article tries to establish whether or not we can consider Buchanan as the author of one or several of these different translations.